Centralized third-party services to improve customer relationship management - Santos, José Luís de Castro Marques dos (2020)
Customer communication has a crucial role in assuring a trustful and reliable relationship with a brand. In many cases, customer communication is held by many different service providers in order to use different expertise. Such services channel communication, segment targets, improve recommendations, among others. However, having different services on separate platforms may lead to some issues: - the campaign creation and management must be done on different platforms; - the learning curve will be different for each service; - the more services we have, the more resources we need to manage and use them; All the mentions points create different limitations for large companies. CRM software providers are reluctant to offer third party services integrations to their clients, considering that they would rather sell the full feature package. To address this issue in the industry, we propose working to find a way to integrate third-party services on one leading service.